23=x+43

Simple and best practice solution for 23=x+43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=x+43 equation:


Simplifying
23 = x + 43

Reorder the terms:
23 = 43 + x

Solving
23 = 43 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
23 + -1x = 43 + x + -1x

Combine like terms: x + -1x = 0
23 + -1x = 43 + 0
23 + -1x = 43

Add '-23' to each side of the equation.
23 + -23 + -1x = 43 + -23

Combine like terms: 23 + -23 = 0
0 + -1x = 43 + -23
-1x = 43 + -23

Combine like terms: 43 + -23 = 20
-1x = 20

Divide each side by '-1'.
x = -20

Simplifying
x = -20

See similar equations:

| 0.8(6x+7)=2.7-(x-3) | | 5=-2xX+27 | | (1/4)w=16 | | 0.14w=0.70forw | | -5(-3-8x)=15+2x | | 2k-(2.1k-7.5)=28.6 | | x=x+5cosx | | 3x+2x-34+3= | | 2x-4(x-4)=6+3x+12 | | 9x-13=x+5 | | 4(4+4x)=-4+6x | | 2(n-9)=6+n-3(1+n) | | 6ln(x+3)-3lnx= | | 8(5t+1)-15=t-(t+6) | | 55(x+1)=48 | | 6(1-7x)=6-8x | | 15*7+(10-7)=141 | | 6(6t+1)-9=t-(t+2) | | 2y-3=12y | | 3k^2+2k-3=0 | | y=3x-10 | | -x+5(-6x+4)=-197 | | 5x+5=59 | | 2(3n-1)= | | 5p-7=55-5p | | -8-8p=-p-8p-5 | | 55t*2t=6.50+405.50 | | 1/4f-4=1 | | -97=-7-6(5-5x) | | 63=p-19 | | 4y-9+40=5y | | 1/2(4x)(6x-5)= |

Equations solver categories